Managing displacement : refugees and the politics of humanitarianism - Hyndman, Jennifer (Borderlines (Minneapolis, Minn.), 2000)
In this analysis of how refugee relief services work in places such as Kenya and Somalia, Hyndman uses unique insider knowledge both to challenge the political and cultural assumptions of current humanitarian practices and to expose the distancing strategies that characterize present operations.